Keputusan Pembelian Ditinjau dari Brand Ambassador, Viral Marketing dan Brand Trust: - Galuh Pramesti, Lusiana Putri; Aryati, Ida; Hamidah, Raisa Aribatul (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to ascertain the impact of brand ambassadors on consumer decisions. To ascertain how viral marketing influences consumers' purchase choices. To ascertain how purchasing decisions are impacted by brand trust. To assess the combined effects of viral marketing, brand trust, and brand ambassadors on purchasing choices. The research iis descriptive quantitative in nature. Consumers of azarine were the subject of this study in Surakarta. The sample size for this study is 100 respondents. Purposive sampling is the sampling method that is employed. data gathering through questionnaires. The data analysis methods employed are, F test, t test, multiple llinear regression test and the coefficient of determination. According to the study's findings, brand ambassadors in Surakarta have a strong beneficial influence on consumers' decisions to buy Azarine products. Viral marketing has a notable favorable impact on Azarine product purchases in Surakarta, at least in part. In Surakarta, brand trust has a substantial beneficial impact on consumers' decisions to buy Azarine products. Brand advocates, virall marketing, and brand trust all have a substantial beneficial iimpact on Surakarta consumers' decisions to buy Azarine products. Keywords: Brand Ambassador, Virall Marketing, Brand Trust, Purchase Decision